Rasionalitas Kenabian Menurut Fakhrudin al-Razi - Qois Azizah Bin Has (University of Darussalam Gontor, Indonesia, 2019)
This paper discusses the prophetic rationality according to Fakhruddin al-Razi. al-Razi seeks to prove the prophetic truth of the mind to oppose the assumption that prophetic is a matter that is not necessarily believed to be true. This assumption due to the prophetic is not considered something that could be resourceful and intangible. It was conceptualized by Muhammad Ahmad ibn al-Ruwandi (late 3rd century H) and Abu Bakar Muhammad ibn Zakariya al-Razi (865-925 A.D.). According to both view the Prophet’s position can be substituted human sense as long as it is true and be able to develop human's knowledge. Thus the Prophet with all his functions as a messenger of God is no longer needed in life. It is certainly contrary to that of Islamic taught. For this reason al-Razi rejected the concept and proved that the prophetic was true in Revelation and reason. In his study, al-Razi used two elements of revelation and philosophy to prove the prophetic concept. It is because revelation is the source of everything and philosophy as a tool of thinking with reason. Systematically, the concept of the prophetic rationality of al-Razi is able to demonstrate that the prophetic is not only the dogma of religion, but it is also an obligatory truth.